2008
DOI: 10.1002/jgt.20353
|View full text |Cite
|
Sign up to set email alerts
|

Excluding a bipartite circle graph from line graphs

Abstract: We prove that for fixed bipartite circle graph H, all line graphs with sufficiently large rank-width (or clique-width) must contain an isomorphic copy of H as a pivotminor. To prove this, we introduce graphic delta-matroids. Graphic delta-matroids are minors of delta-matroids of line graphs and they generalize graphic or cographic matroids. IntroductionRobertson and Seymour [20] proved that every graph of sufficiently large tree-width must contain a minor isomorphic to a fixed planar graph. Their theorem was g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…We remark that with different methods, Oum [7] showed that the rank-width of L(G) is exactly one of bw(G) − 2, bw(G) − 1, or bw(G) if G is 2-connected.…”
Section: Main Theoremmentioning
confidence: 99%
“…We remark that with different methods, Oum [7] showed that the rank-width of L(G) is exactly one of bw(G) − 2, bw(G) − 1, or bw(G) if G is 2-connected.…”
Section: Main Theoremmentioning
confidence: 99%
“…One may wish to have a structure theorem describing graphs with no fixed vertex-minors or no fixed pivot-minors in order to extend these theorems to other forbidden graphs. Indeed, Oum [28] conjectured the following. A graph is a circle graph if it is an intersection graph of chords in a circle.…”
Section: Further Discussionmentioning
confidence: 98%
“…Vertex-minors and pivot-minors are graph containment relations introduced by Bouchet [3,4,5,6] while conducting research of circle graphs (intersection graphs of chords in a cycle) and 4-regular Eulerian digraphs. Furthermore, these graph operations have been used for developing theory on rank-width [20,26,27,28,29]. We review these concepts in Section 2.…”
Section: Introductionmentioning
confidence: 99%
“…(For rank-width and vertex-minors, see Oum [33].) This conjecture is proved for line graphs by Oum [34].…”
Section: Introductionmentioning
confidence: 93%